The Influence of Product Quality and Price on Consumer Satisfaction at Lotus Restaurant Grand Savero Hotel Bogor - Riani Prihatini Ishak; Irhamna Sabilla; Nicko Gana Saputra; Sarah Aqilah Azmadi (Jurnal Penelitian Pariwisata, 2026)
This study addresses the challenge of understanding factors influencing consumer satisfaction in the hospitality industry, focusing on product quality and price at Lotus Restaurant, Grand Savero Hotel Bogor. The research aims to determine the individual and combined effects of these variables on customer satisfaction. Employing a quantitative methodology, data were collected from 100 respondents and analyzed using multiple linear regression. The findings reveal that product quality significantly impacts consumer satisfaction, while price does not show a significant individual effect. However, when examined simultaneously, both product quality and price demonstrate a significant influence on consumer satisfaction. The coefficient of determination (R²) indicates that these two factors account for 58.2% of the variance in customer satisfaction. The study concludes that while product quality is a crucial determinant of consumer satisfaction, while pricing strategies may require reassessment. The insignificance of price suggests that customers prioritize perceived product quality over cost considerations in a hotel dining context. The combined effect of both variables suggests a complex interplay in shaping customer experiences. These insights can guide the restaurant management focusing on maintaining consistent product quality while adjusting pricing strategies to better reflect customer value perceptions. Keywords: product quality, price, consumer satisfaction